Transverse Rectus Abdominis Muscle Flow-Through to Free Fibula Flap for Lumbar Spinal Reconstruction in a Pediatric Patient: A Case Report. Issue 1 (24th January 2022) - Moores, Neal G.; Luo, Jessica; Pires, Giovanna; Moss, Whitney; Short, Scott; Bollo, Robert J.; Randall, R. Lor; Agarwal, Jayant P.
Abstract : Case: A 7-week-old girl presented with a recurrent primitive myxoid mesenchymal tumor of infancy requiring extensive resection of lower back musculature, L3–S2 vertebral bodies, and left L5 nerve root. Reconstruction consisted of transverse rectus abdominis muscle (TRAM) flow-through to free fibular flap to reconstruct the bony defect and fill the soft-tissue void. One-year postoperative imaging revealed a well-incorporated fibula graft. At the 30-month follow-up, the patient can bear weight on the autograft while sitting upright, allowing for efficient ambulation with a wheelchair. Conclusion: TRAM flow-through to free fibular flap is an efficacious reconstructive method for a multilevel vertebral spinal defect in a pediatric patient.